Establishing an Approach to Mechanical Ventilation - Thomas E Stewart (Canadian Respiratory Journal)
Technology in the intensive care environment has progressed at an exponential rate. This progression has particularly been noticeable in relation to mechanical ventilation where advancements have arguably surpassed improvements in patient morbidity and mortality. Ventilator-induced lung injury (VILI), which occurs secondary to lung overdistension and underinflation, may largely be responsible for this discrepancy. No matter which of the vast number of modes of mechanical ventilation are employed, simple principles can be followed that will prevent the development of VILI. A lung protective ventilatory approach incorporates the prevention of oxygen toxicity and the avoidance of lung over- and underinflation, while frequently using permissive hypercapnia. By establishing a lung protective approach early in the management of ventilated patients, the morbidity and mortality associated with respiratory failure may finally be reduced.